Tuesday morning coaching : eight simple truths to boost your career and your life - Cottrell, David, 1953- (Dallas, TX : CornerStone Leadership Institute, 2010)
"What is the key to success? There isn't one. Long-term success is not the result of one defining change or doing one thing well. It comes from embracing several small, simple yet powerful truths. In this follow-up to his best-selling Monday Morning book series, author David Cottrell shares how you can use the simple truths that are all around you to reboot your career and take you life to the next level."-back cover.
"A mentor's perspective on reigniting success."-cover page.
Keywords: Success in business; Supervision of employees; Leadership